Analysis of the Influence of Gasoline Adulteration on Lubricant Degradation and Internal Combustion Engine Performance - Gonçalves, Aparecido Carlos [UNESP]; Ferreira, Ronaldo Lourenço [UNESP]; Preto, Eduardo [UNESP]; Karmouche, Diogo [UNESP]; Chavarette, Fábio Roberto [UNESP]; Outa, Roberto [UNESP] (American Chemical Society (ACS), 2022)
In internal combustion engines, studies of the effects of fuel adulteration focus on problems that occur in the fuel system and pollutants, but little attention is paid to lubricants. Some of these research studies are focused on detecting adulteration rather than the impact of this tampering on the internal combustion engine and lubricant degradation. This work evaluates, in addition to the problems in the supply system, the early degradation of the lubricant from the physical and chemical changes it undergoes when using adulterated gasoline in an internal combustion engine. For that, a 160cc Honda stationary engine mounted on a bench and connected to an alternator through a transmission belt was used. Fuels adulterated with ethanol, kerosene, and thinner were used in proportions of 5, 10, 15, and 20%. The cycles were 40 h each, which is equivalent to approximately 2000 km covered. To measure the engine time and rotation, a tachometer/hourmeter was used, where the time of each cycle was recorded. Particle quantifier analysis (PQA) tests and infrared spectrometry (sulfation, nitriding, oxidation, and total acid number (TBN)) were performed, in addition to changes in engine behavior in relation to rotation. The results showed changes in rotation according to the concentration and type of contaminants. Engine wear was small for the 2000 km covered. The sulfation, nitriding, oxidation, and TBN levels were altered, indicating the degradation of the lubricating oil.